The Effect of Education, Communication, And Leadership on Performance Employee PT Shopee Indonesia - Monica Valerie; Deni Faisal Mirza; Nur M Ridha Tarigan (International Journal Of Economics Social And Technology, 2023)
Objective study This test influence Education, communication, And Leadership to Performance Employee PT Shopee In Jakarta South, Good in a manner Partial nor simultaneous. This research studies descriptive quantitative. The population of this research is PT Shopee employees in South Jakarta number 1,600 people. Sample this research obtained by 94 people with the formula Slovin and the sampling technique is the technique simple random sampling. Method statistics used is analysis sis multiple linear regression. Results calculation testing in a manner Partial obtained mark t count 3.058 > t table 1.98638 and value significant of 0.003 <0.05, value t count 2.689 > t table 1.98638 and value significant as big 0.009 < 0.05, value t count 5.820 > t table 1.98638 and value significant of 0.001 <0.05. Results calculation testing in a manner simultaneous obtained mark F count 113.436 > F table 2.71 and value significant 0.000 <0.05. The magnitude coefficient determination of 78.4% and the remaining 21.6% are explained by other variables that have not been examined in this study such as motivation, environment work, and compensation. The conclusion of this research is in a manner simultaneous and partial Education, Communication, and influence influential significant on Performance Employee PT. Shopee In South Jakarta.